Temporal variation in optical properties of chromophoric dissolved organic matter (CDOM) in Southern California coastal waters with nearshore kelp and seagrass. (5th October 2015) - Clark, Catherine D.; De Bruyn, Warren J.; Aiona, Paige D.
Abstract: Optical properties of chromophoric dissolved organic matter (CDOM) were measured in surf zone waters in diurnal field studies at a Southern California beach with nearshore kelp and seagrass beds and intertidal plant wrack. Absorption coefficients ( a CDOM (300 nm)) ranged from 0.35 m −1 to 3.7 m −1 with short‐term variability < 1 h, increases at ebb and flood tides and higher values (6 m −1 ) during an offshore storm event. Spectral slopes ( S ) ranged from 0.0028 nm −1 to 0.017 nm −1, with higher values after the storm; S was generally inversely correlated with a CDOM (300 nm). 3‐D excitation–emission matrix spectra (EEMs) for samples with lower S values had humic‐type peaks associated with terrestrial material (A, C), marine microbial material (M) and protein peaks, characteristic of freshly produced organic material. Samples with high S values had no or reduced protein peaks, consistent with aged material. Fluorescent indexes ( f450/f500 >2.5, BIX > 1.1) were consistent with microbial aquatic sources. Leachates of senescent kelp and seagrass had protein and humic‐type EEM peaks. After solar simulator irradiation (4 h), protein peaks rapidly photochemically degraded, humic‐type peak C increased in intensity and peak M disappeared. Optical characteristics of kelp leachates were most similar to field samples, consistent with minimal contributions from sea grass, a small component of the biomass at this site. Increases in a CDOM (300 nm) with decre a ses in S are attributed to the input of freshly produced autochthonous organic material at ebbing and flooding tides, from exudation and microbial processing of senescent plant wrack and nearshore macroalgal vegetation. Other allochthonous sources are hypothesized to be ground water seepage and terrestrial runoff.